What is the role of intra-operative fluoroscopic measurements to determine tibial tunnel placement in anatomical anterior cruciate ligament reconstruction? - Kasten, Philip; Szczodry, Michal; Irrgang, James; Kropf, Eric; Costello, Joanna; Fu, Freddie H. (Knee surgery, sports traumatology, arthroscopy, 2010)
The hypothesis for this study was that intra-operative fluoroscopic measurements can be used to determine tibial tunnel placement during anatomic anterior cruciate ligament (ACL) reconstruction. The anteromedial (AM) and posterolateral (PL) bundle insertion sites were marked with a thermal device and measured in a consecutive cohort of 67 patients undergoing anatomical ACL reconstruction. For double bundle reconstruction, guide pins were passed in the center of the AM and PL tibial footprints. For single bundle (SB) reconstruction a guide wire was placed between the center of AM and PL footprints. Subsequently, the position of the centers of the AM and PL insertion sites were measured on standardized lateral intra-operative fluoroscopic images. The center for the AM bundle was found to be at 31% (range 20-42%) of the AP distance on the medial joint line and at 35% (range 23-42%) of the AP distance on the Amis and Jakob line. The center of the PL bundle was at 48% (range 37-59%) of the AP distance on the medial joint line and 48% (range 39-58%) of the AP distance on the Amis and Jakob line. The center of the tibial tunnel in the SB group (n = 15) was at 42 and 41% in relation to the medial joint line and the Amis and Jakob line, respectively. Because a significant anatomic variation exists between patients, the decision with respect to tunnel placement should not be merely based on intra-operative fluoroscopic images.
Gesehen am 07.03.2023